Cost - efficiency and Share Performance: Evidence from ASEAN-6 banks - Vu, Chau (2019)
This study empirically investigates the cost efficiency of 88 banks in six largest economies in the Association of Southeast Asian Nations (ASEAN-6) including Indonesia, Malaysia, Philippines, Singapore, Thailand and Vietnam over the period of 2012-2017 by employing a parametric method Stochastic Frontier Analysis (SFA). We find out that comparing with banks in domestic market, banks in ASEAN-6 are relatively cost efficient, with efficiency scores ranging from 0.9030 to 0.9763. Furthermore, the average efficiency scores are also quite consistent from year to year. However, while comparing cross-country, efficiency varies greatly. Singaporean banks are the most efficient while banks from Philippines are the least efficient. Our results also indicate that larger banks were more efficient than smaller banks. We then continue to link bank cost efficiency with their subsequent share prices by applying Fixed Effects and Generalised Method of Moments (GMM). The study suggests that there is positive relationship between change in cost efficiency and share returns while using fixed effects regression. However, this relationship was diminishing when applying GMM.